PENGARUH KOMPETENSI DAN INDEPENDENSI AUDITOR TERHADAP KUALITAS AUDIT - PERDANA HANDOYO, ANDY (Berkala Ilmiah Mahasiswa Akuntansi)
Research entitled â€œThe Influence of The Competence and Independence of The Auditor to Audit Qualityâ€ aims to test and analyze the effect of the competence and independence of the auditor to audit quality. The object of the research is the registered public accounting and working in public accounting (PAO) at Surabaya on the condition that minimum has been working for six months in public accounting. Research data obtained from a questionnaire to the number of data fields data as much as 59 people respondents. Data analysis technique that is used is to use the test validity, reliability, test classic assumptions, and multiple linear regression with the help of the program SPSS for windows. The result showed that a variable whose competence be reviewed of experience and the knowledge it has some positive effects against the quality of an audit , while pendency reviewed from old the relation of with clients , pressure from clients , analysis from a peer the auditors , and services non an audit not influential against the quality of an audit.